Mining Sludge Utilization as Medium Growth for Revegetation Plants through Seed Germination Test - Muhamad Ramdhanny Pratama; Irdika Mansur; Omo Rusdiana (Jurnal Sylva Lestari, 2023)
The limited topsoil stock is one of the post-mining reclamation problems that will directly impact the company’s business processes. One solution that can be considered to reduce production costs is the utilization of unused materials around the mine. The settling pond sludge contains nutrients and can be used as a growing medium for plants to replace topsoil. This study examined the potential utilization of settling pond sludge through germination and sprout viability tests. This study used a completely randomized design with four composting treatments, namely 0%, 25%, 50%, and 75%. The number of replications was ten times and applied to several species of revegetation plants, namely Acacia mangium, Senna siamea, Falcataria moluccana, and Albizia saman, so there were 160 experimental units in total. The results showed that the settling pond sludge has organic matter reserves and low nitrogen content but is rich in P and element reserves of P and K. The physical texture of settling pond sludge was still suitable as a medium for plant growth. The addition of compost as a mixture of settling pond media had a significant effect on germination and germination viability but had no significant effect on the parameters of the germination rate. The increase in compost composition in the settling pond media mixture positively affected germination and germination survival. Based on this research, it is known that settling pond sludge can be used as a medium for growing revegetation plants. In general, the media with the addition of 50% and 75% compost gave the best germination response and viability. Keywords: Compost, post-mining reclamation, revegetation, seed germination test, settling pond sludge